SKALA USAHA MINIMUM PADA USAHATANI TEMBAKAU (Nicotiana tabacum) KABUPATEN REJANG LEBONG - Utama, Satria Putra; Irawan, Andi; Marito H, Butmen (Jurnal AGRISEP, 2006)
Tobacco  was one of   priority  commodity  in Rejang  Lebong  district  to develop,  its supported  by suitable micro climate and farmer behavior so long. The research  were objected  to analyze the influencing factors on produdion  and minimum  economic scale of tobacco  farming system  at Rejang Lebong District. These tried to answer thorugh the cob-douglas  and break even point  analyses. The research  showed  that area  (x 1),  TSP fertilizer  (x3),  ZA  fertlizer  (x4)  significantly  influence  to  tobacco  production.   Minimum economic  scale of tobacco  farming system  around  0.07 ha but farmers  scale  about  0.49 ha. It meaned that farmet tobacco were already in comerdal/economic   scale. Improving  the prcxluction  could be attained thorugh  extensification  and intesification  . extensification  in the way of extended  the  croping  area, while intesification  by improving  fertilizers  of TSP and ZA  to optimal  level  of usage.  others  factors  should  be another  farmer  focus to increas  prcxluction such  quality of seed,  integrated  and environmental  pestici~e and so forth.